The ups and downs of bilingualism: A review of the literature on executive control using event-related potentials - Antoniou, Kyriakos (My University, 2023)
Whether bilingualism enhances executive control (EC) is controversial. This article reviews 24 studies on the bilingual EC effect using event-related potentials (ERPs). It evaluates the evidence based on considerations of neural efficiency, different EC theories, and accounts regarding the locus of the bilingual effect. The review finds some evidence for a positive bilingual impact. This is more consistent for the P3 and response-locked ERPs. Moreover, when considering each component independently, evidence primarily supports a monitoring and secondarily an inhibition locus. Additionally, an N2/ERN (error-related negativity) dissociation (no bilingual N2 effect but positive ERN impact, evident as smaller ERN), coupled with the P3 results, suggest that monitoring may not be the (only) locus of a bilingual effect but (an)other post-monitoring mechanism(s). Attention disengagement also receives some support. Finally, results across studies are largely consistent with the Bilingualism Anterior to Posterior and Subcortical Shift model (BAPSS): Bilingual effects, when found, often manifest as shorter latencies, larger components or wider amplitude effects during earlier (N2, P3) but smaller components or narrower effects during later processing (stimulus-locked negativities and response-locked components). However, this evidence is not unequivocal. Many bilingual-monolingual comparisons reveal null or some suggest negative or opposite to prediction bilingual effects. Second, the scant evidence about which bilingual experiences impact EC is, generally, unclear, while some evidence indicates negative effects. Third, BAPSS is often not confirmed when multiple components are examined within subjects. Finally, this literature is challenged by confounds and small samples. Further research is required to conclude a positive bilingual effect on EC in ERPs.
Keywords: Attention and executive control; Electrophysiology; ERPs and working memory/attention; Task switching or executive control